Prenatal Diagnosis and Perinatal Outcomes of Congenital Megalourethra: A Multicenter Cohort Study and Systematic Review of the Literature. (7th October 2015) - Moaddab, Amirhossein; Sananes, Nicolas; Hernandez-Ruano, Simone; Werneck Britto, Ingrid Schwach; Blumenfeld, Yair; Stoll, François; Favre, Romain; Ruano, Rodrigo
Abstract : Objectives: The purpose of this study was to evaluate the prenatal findings and postnatal outcomes in fetuses with congenital megalourethra. Methods: This retrospective study reviewed our experience and the literature between 1989 and 2014. Prenatal findings were evaluated and compared with postnatal findings, including neonatal mortality and abnormal renal function (need for dialysis or renal transplantation). Results: Fifty fetuses with congenital megalourethra were analyzed, including 6 cases diagnosed in our centers. Most cases (n = 43 [86.0%]) were diagnosed in the second trimester. Only 1 case was diagnosed in the first trimester, whereas 6 cases (12.0%) were diagnosed in the third trimester. Thirty‐five fetuses (70.0%) survived. Bilateral hydroureters were associated with perinatal death ( P = .024). Among the survivors, 41.9% of the neonates had renal impairment. The following factors were associated with postnatal renal impairment: presence of severe oligohydramnios/anhydramnios ( P = .033), bilateral hydronephrosis ( P = .008), and earlier gestational age at delivery ( P = .022). Conclusions: In fetal megalourethra, bilateral hydroureters, bilateral hydronephrosis, and severe oligohydramnios/anhydramnios are associated with neonatal mortality and renal impairment.